Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1017/s0022112006000851
|View full text |Cite
|
Sign up to set email alerts
|

The rolling up of sheets in a steady flow

Abstract: The mechanism of reconfiguration of broad leaves subjected to wind loading is investigated. Circular plastic sheets cut along a radius are immersed in a water flow. They roll up into cones when held at their centres. The opening angle of the cone and the drag force exerted on the sheet are measured as a function of the flow velocity and of the sheet bending rigidity. The cone becomes sharper when the velocity increases or when the sheet stiffness decreases; the reconfiguration leads to a decrease in the drag c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 10 publications
6
63
0
Order By: Relevance
“…31,[34][35][36][37] Analogous artificial systems were studied, including numerical models which reproduce experimental measurements on a fibre subjected to a soap film, 38,39 a flexible plate in air 40 or water 41,42 flow, and artificial leaves. 43,44 Experimental data are observed to collapse on a single reconfiguration curve so that…”
Section: -2 Barsu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…31,[34][35][36][37] Analogous artificial systems were studied, including numerical models which reproduce experimental measurements on a fibre subjected to a soap film, 38,39 a flexible plate in air 40 or water 41,42 flow, and artificial leaves. 43,44 Experimental data are observed to collapse on a single reconfiguration curve so that…”
Section: -2 Barsu Et Almentioning
confidence: 99%
“…4,38,42,43,45 However, in rivers, canopies are sets of plants close to each other, giving rise to a strong screening effect, so that plants in canopies do not behave like single plants. 46,47 There is also an increasing interest in theoretical models for drag force acting on poro-elastic systems.…”
Section: -2 Barsu Et Almentioning
confidence: 99%
“…Static and dynamic reconfiguration in response to increasing flow velocity often leads to deviation from a quadratic relationship between the drag and flow velocity, even at fairly high Reynolds numbers (e.g., Armanini et al 2005;Vogel 1989, 1994, 2009, Sand-Jensen 2003Statzner et al 2006). Despite plant leaves playing an important role in drag control at larger scales of patches and patch mosaics (e.g., Järvelä 2002;Wilson et al 2003), very little is known about the physical mechanisms involved (de Langre 2008;Ennos 1999;O'Hare et al 2010;Sand-Jensen 2003;Schouveiler et al 2006;Vogel 1989Vogel , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…As Reynolds number (Re) was increased from 10 to 800, Zhu found that the exponents of the power laws decreased monotonically from approximately 2 towards 4/3. Schouveiler and Boudaoud (Schouveiler and Boudaoud, 2006) showed experimentally that flexible sheets with rigid tethers can roll up into cone shapes in steady flow, also reducing the drag acting upon them. Gosselin et al (Gosselin et al, 2010) considered flexible plates with rigid tethers in a steady wind tunnel.…”
Section: Introductionmentioning
confidence: 99%